Cyclotron resonance conditions in current-carrying plasmas - Grishanov, N.I.; Azarenkov, N.A. (Вопросы атомной науки и техники, 2018)
The resonant cyclotron wave-particle interactions in the cylindrical current-carrying plasma and axisymmetric
toroidal plasma models for large aspect ratio tokamaks with circular, elliptic and D-shaped cross-sections of the
magnetic surfaces have been analyzed. The corresponding conditions are derived by solving the linearized Vlasov
equations for perturbed distribution functions of plasma particles, accounting for the geometry of a confinement
magnetic field in the zero-order over magnetization parameters. It is shown that the Doppler shift at the cyclotron
resonance conditions in the current-carrying plasmas is entirely different from ones in uniform magnetic field. Проаналізовано умови резонансної взаємодії заряджених частинок з хвилями в плазмовому циліндрі зі
струмом та в тороідальних аксіально-симетричних моделях плазми для токамаків з круговим, еліптичним і
D-подібним перерізами магнітних поверхонь. Відповідні резонансні умови отримано шляхом розв'язку
лінеаризованих рівнянь Власова для збурених функцій розподілу плазмових частинок з урахуванням
геометрії утримуючого магнітного поля в нульовому наближенні за параметрами замагніченості. Доведено,
що доплерівський зсув в умовах циклотронних резонансів у плазмі зі струмом істотно відрізняється від
аналогічних оцінок для плазми в однорідному магнітному полі. Проанализированы условия резонансного взаимодействия заряженных частиц с волнами в плазменном
цилиндре с током и в тороидальных моделях плазмы для токамаков с круговым, эллиптическим и Dобразным сечениями магнитных поверхностей. Соответствующие резонансные условия получены путем
решения линеаризованных уравнений Власова для возмущенных функций распределения частиц с учетом
геометрии удерживающего магнитного поля в нулевом приближении по параметрам замагниченности.
Показано, что доплеровская сдвижка в условиях циклотронных резонансов в токопроводящей плазме
существенно отличается от аналогичных оценок в плазме с однородным магнитным полем.